Biotechnology and Pasta-Making: Lactic Acid Bacteria as a New Driver of Innovation - Capozzi, Vittorio; Russo, Pasquale; Fragasso, Mariagiovanna; de Vita, Pasquale; Fiocco, Daniela; Spano, Giuseppe (Frontiers in Microbiology, 2012)
Cereals-derived foods represent a key constituent in the diet of many populations. In particular, pasta is consumed in large quantities throughout the world in reason of its nutritive importance, containing significant amounts of complex carbohydrates, proteins, B-vitamins, and iron. Lactic acid bacteria (LAB) are a heterogeneous group of bacteria that play a key role in the production of fermented foods and beverages with high relevance for human and animal health. A wide literature testifies the multifaceted importance of LAB biotechnological applications in cereal-based products. Several studies focused on LAB isolation and characterization in durum wheat environment, in some cases with preliminary experimental applications of LAB in pasta-making. In this paper, using sourdough as a model, we focus on the relevant state-of-art to introduce a LAB-based biotechnological step in industrial pasta-making, a potential world driver of innovation that might represent a cutting-edge advancement in pasta production.